Assessment of risk factors associated with pre-term labour in Tertiary care Hospitals, Lahore (Journal of Fatima Jinnah Medical University, 2021)
Background: Pakistan has one of the highest rates of preterm births, nearly 16 for every 100 babies born. Around 4% of these premature babies, are at highest likelihood of death. The objective of this study was to assess association of multiple risk factors with preterm birth in Pakistani women.Patients and methods:  An analytical cross-sectional study was carried out in Obstetrics and Gynecology Department of Akhtar Saeed Trust Hospital and Farooq Hospital, West Wood Branch, Lahore from October 2018 to December 2019. Total 116 pregnant females who gave birth to preterm babies with gestational age between 20-37 weeks were included. Data about patients’ socio-demographic profile, previous obstetric history and current gestational profile was collected using closed ended structured questionnaire. Variables were presented in the form of frequency tables. Chi-square and Fisher exact test were applied to establish association of various risk factors and preterm presentation of patients’ in hospital. A p-value ≤ 0.05 was taken as significant.Results: Out of 116 participants, 49 (42.2%) were aged between 20-25 years, 47 (40.5%) were illiterate. Of the total sample 60 (51.7 %) participants were obese (BMI >30). Eighty-two (70.7%) patients were multigravida and 65 (56.1%) gave the history of previous cesarean section. Significant association was found between preterm birth and multi-parity (p=0.001), previous history of abortion (p=0.000), intrauterine death (p=0.001), infertility (p=0.04), cesarean-section (p=0.000), and inter-pregnancy interval of less than 24 months (p=0.007). Other significant factors associated with preterm labour were urinary tract infections (p=0.001), documented fever more than 101oF (p=0.000), anemia (p=0.000), singleton pregnancy (p=0.000) and cephalic fetal presentation (p=0.002), during current pregnancy.Conclusion: Multi-gravidity, history of abortion, intrauterine death, previous infertility, cesarean-section, inter-pregnancy interval of less than 24 months, UTI, genital tract infection, anemia, singleton pregnancy and cephalic fetal presentation during current pregnancy were observed to be significantly associated with preterm births.
Keywords: Preterm birth; Risk factors; Multi-gravidity; Intrauterine death; Abortion; Cesarean-section; Anemia